A Quasi-Experiment on the Effectiveness of Using ChatGPT in Improving High School Students' Understanding of Historical Concepts - Hasan; Suyuti; Minarni Nongtji; Ika Nur Jayanti; Ismail (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Advances in artificial intelligence (AI) present new opportunities in education, including history learning. ChatGPT, an AI-based application, has the potential to help students understand abstract historical concepts, although its effectiveness remains to be studied. This study aims to evaluate the effect of using ChatGPT on high school students' understanding of historical concepts through a quasi-experimental pre-test and post-test design. The research sample was purposively selected from several high schools, with the research stages including instrument preparation, implementation of learning using ChatGPT, and data analysis through statistical tests. This research uses a quasi-experimental method with a pre-test-post-test control group design. Showed a significant improvement in the learning outcomes of students using ChatGPT compared to students who participated in conventional learning. Analysis of pretest and posttest data showed that the experimental group experienced a greater increase in understanding of historical material, particularly in their ability to connect events, figures, and time contexts more logically. This study is at Technology Readiness Level (TKT) 4–5, indicating that the technology is mature but still requires further validation in a school context. The implications of this study suggest that the use of artificial intelligence technology can be an alternative, innovative, and adaptive learning strategy to meet the needs of students in the digital age. The findings indicate that ChatGPT can help students quickly access historical information, provide contextual explanations, and encourage more independent and inquiry-based learning interactions.